Pemanfaatan Class Point untuk Membuat Media Pembelajaran Interaktif “Energi dan Perubahannya” dengan Kuis Langsung untuk Kelas 5 SD (International Forum of Researchers and Lecturers, 2026)
One effort to enhance students’ engagement, learning interest, and conceptual understanding in Natural Science learning at the elementary school level is through the use of interactive learning media that are aligned with learners’ characteristics. Interactive learning media are considered capable of creating a more active and meaningful learning environment. This study aims to evaluate the use of ClassPoint as an interactive learning medium based on live quizzes on the topic of Energy and Its Transformations for fifth-grade elementary school students. The research method employed is a Systematic Literature Review (SLR) by examining various relevant and credible scientific articles obtained from the Google Scholar, Garuda, and Directory of Open Access Journals (DOAJ) databases. The findings indicate that the use of ClassPoint in science learning can significantly increase students’ participation, activeness during the learning process, and learning motivation. In addition, students’ responses to the use of ClassPoint generally show positive attitudes, as learning is perceived to be more engaging, interactive, enjoyable, and easier to understand. However, the successful implementation of ClassPoint in elementary school science learning requires adequate facilities and infrastructure as well as teacher training. The challenges encountered include limitations in technological infrastructure, the readiness of supporting devices, and teachers’ ability to effectively optimize the features of learning media.